Verti-zontal differentiation in monopolistic competition - Francesco Di Comite; Jacques-François Thisse; Hylke Vandenbussche (National Bank of Belgium, 2011)
The recent availability of trade data at a firm-product-country level calls for a new generation of models able to exploit the large variability detected across observations. By developing a model of monopolistic competition in which varieties enter preferences non-symmetrically, we show how consumer taste heterogeneity interacts with quality and cost heterogeneity to generate a new set of predictions. Applying our model to a unique micro-level dataset on Belgian exporters with product and destination market information, we find that heterogeneity in consumer tastes is the missing ingredient of existing monopolistic competition models necessary to account for observed data patterns.
Keywords: D43; F12; F14; L16; 330; Heterogeneous firms; Product Differentiation; Monopolistic Competition; Nonsymmetric varieties; Produktdifferenzierung; Konsumentenverhalten; Monopolistischer Wettbewerb; Industrieökonomik; Belgien